Kontribusi Produk Pembiayaan Kelompok Syariah Yang Tepat Terhadap Pemberdayaan Ekonomi Perempuan - Resta Rentika Maharani; Erike Anggraeni; Ridwansyah Ridwansyah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the contribution of appropriate Islamic group financing products to women’s economic empowerment. Women’s economic empowerment is a critical issue in sustainable development, particularly in improving women’s access to financial resources, business opportunities, and economic decision-making. This research adopts a qualitative approach using a literature review method, examining various academic sources such as journal articles, books, and relevant reports. Data were collected through academic databases and analyzed using descriptive and content analysis techniques to identify patterns, relationships, and key findings. The findings reveal that Islamic group financing significantly contributes to increasing women’s income, economic independence, and decision-making capacity. The group-based financing model, which applies joint liability mechanisms, has proven effective in reducing financing risks while strengthening social cohesion and mutual support among members. Furthermore, Islamic financial principles such as justice, profit-sharing, and the prohibition of riba provide a more ethical and inclusive framework for women to access financial services. However, the effectiveness of financing largely depends on the appropriateness of the products to women’s needs, including flexible repayment schemes, simple contract structures, and the availability of mentoring and financial literacy programs. This study concludes that appropriately designed Islamic group financing products can serve as an effective instrument in promoting sustainable women’s economic empowerment. Therefore, a holistic and gender-sensitive approach is essential in developing Islamic financial products to ensure more optimal and inclusive outcomes.